Non-isocyanate polyurethanes: synthesis, properties, and applications - Rokicki, Gabriel; Parzuchowski, Paweł G.; Mazurek, Magdalena (Polymers for advanced technologies, 2015)
Conventional polyurethanes are typically obtained from polyisocyanates, polyols, and chain extenders. The main starting materials—isocyanates used in this process—raise severe health hazard concerns. Therefore, there is a growing demand for environment‐friendly processes and products. This review article summarizes progress that has been made in recent years in the development of alternative methods of polyurethane synthesis. In most of them, carbon dioxide is applied as a sustainable feedstock for polyurethane production directly or indirectly. The resulting non‐isocyanate polyurethanes are characterized by a solvent‐free synthesis, resistance to chemical degradation, 20% more wear resistance than conventional polyurethane, and can be applied on wet substrates and cured under cold conditions. Three general polymer synthetic methods, step‐growth polyaddition, polycondensation, and ring‐opening polymerization, are presented in the review. Much attention is given to the most popular and having potential industrial importance method of obtaining non‐isocyanate polyurethanes, poly(hydroxy‐urethane)s, based upon multicyclic carbonates and aliphatic amines. It is evident from the present review that considerable effort has been made during the last years to develop environmentally friendly methods of obtaining polyurethanes, especially those with the use of carbon dioxide or simple esters of carbonic acid. Copyright © 2015 John Wiley & Sons, Ltd.